On the unconditional almost-everywhere convergence of general orthogonal series - Mikhailets, V. A.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The Orlicz and Tandori theorems on the unconditional almost-everywhere convergence, with respect to Lebesgue measure, of real orthogonal series defined on the interval (0; 1) are extended to general complex orthogonal series defined on an arbitrary measure space.